Econometric Modelling of Serbian Current Account Determinants: Jackknife Model Averaging Approach - Petrović, Predrag M (Industrija, 2014)
This research aimed to model Serbian current account determinants for the period Q1 2002 - Q4 2012. Taking into account the majority of relevant determinants, using the Jackknife Model Averaging approach, 48 different models have been estimated, where 1254 equations needed to be estimated and averaged for each of the models. The results of selected representative models indicate moderate persistence of the CA and positive influence of: fiscal balance, oil trade balance, terms of trade, relative income and real effective exchange rates, where we should emphasise: (i) a rather strong influence of relative income, (ii) the fact that the worsening of oil trade balance results in worsening of other components (probably non-oil trade balance) of CA and (iii) that the positive influence of terms of trade reveals functionality of the Harberger-Laursen-Metzler effect in Serbia. On the other hand, negative influence is evident in case of: relative economic growth, gross fixed capital formation, net foreign assets and trade openness. What particularly stands out is the strong effect of relative economic growth that, most likely, reveals high citizens’ future income growth expectations, which has negative impact on the CA.
Keywords: Econometric Model; unit root tests; Jackknife Model Averaging approach; current account determinants; Current account balance